Elucidating the effect of stacking sequence on water absorption, flexural, and impact properties of banana pseudostem fiber?reinforced unsaturated polyester composites - Asyraf M.R.M.; Syamsir A.; Ng L.F.; Sheng D.D.C.V.; Tee L.Y.; Madenci E.; Anggraini V. (Springer Science and Business Media Deutschland GmbH, 2025)
Banana pseudostem fiber has been increasingly utilized as reinforcement for composite materials owing to its numerous advantages, such as low density, high availability, and eco-friendliness. Since banana fiber is generally discarded as waste material, it is considered a potential reinforcing material for developing lightweight and eco-friendly composite materials. The main goal of this research study is to investigate the impact of fiber stacking orientation on the water absorption, flexural, and impact properties of banana pseudostem fiber?reinforced unsaturated polyester (UPE) composites. The banana composites with varying stacking orientations were prepared using the hand layup technique. The fiber stacking orientations of banana composites were 0/0/0, 0/90/0, and ? 45/ + 45/ ? 45. In accordance with the findings obtained, banana composites with a stacking orientation of 0/90/0 possessed the best overall mechanical properties and water penetration resistance. The flexural and impact strengths of banana composites with a stacking orientation of 0/90/0 are 23.98% and 128.03%, respectively, higher than those of banana composites with a stacking orientation of ? 45/ + 45/ ? 45. This shows that arranging the middle fiber layer perpendicular to the top and bottom fiber layers in the composites provided more flexural and impact strengths as well as water absorption resistance to the banana composites. ? The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2024.